2016
DOI: 10.1111/pedi.12379
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin as a marker of cardiovascular risk in children and adolescents with type 1 diabetes

Abstract: OPG may be a potential biomarker of cardiovascular risk in T1D. Implementation of OPG determination in the clinical laboratory setting would be useful in order to better stratify patients and to assess the most adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
2
1
Order By: Relevance
“…Together, these findings confirm that OPG levels are abnormal in adult TS cohorts, in particular those who have underlying aortic dilatation. However, contrary to the study by Fekih et al (45), OPG levels did not correlate with traditional cardiometabolic factors like hypertension, hsCRP, cholesterol levels, or nocturnal hypertension, all of which are associated with TS. Nonetheless, it suggests that OPG levels are a biomarker worth examining in childhood TS in relation to cardiometabolic risk factors and aortic disease.…”
Section: Opg In Tscontrasting
confidence: 99%
See 1 more Smart Citation
“…Together, these findings confirm that OPG levels are abnormal in adult TS cohorts, in particular those who have underlying aortic dilatation. However, contrary to the study by Fekih et al (45), OPG levels did not correlate with traditional cardiometabolic factors like hypertension, hsCRP, cholesterol levels, or nocturnal hypertension, all of which are associated with TS. Nonetheless, it suggests that OPG levels are a biomarker worth examining in childhood TS in relation to cardiometabolic risk factors and aortic disease.…”
Section: Opg In Tscontrasting
confidence: 99%
“…Fekih et al (45) quantified circulating OPG levels in a childhood T1DM cohort ( n  = 143; mean age 12 years) with cardiometabolic risk factors such as prolonged duration (≥4 years) of diabetes, HbA1c ≥ 7%, dyslipidemia, and microalbuminuria (≥30 mg/24 h). Their study revealed that OPG levels were significantly higher ( p  < 0.0001) in the T1DM cohort.…”
Section: Opg In Tsmentioning
confidence: 99%
“…(41)(42)(43) Importantly, OPG has also been associated with cardiovascular risk, ulcer development, and peripheral neuropathies. (44)(45)(46)(47) The mechanism by which OPG contributes to these conditions may be through the inhibition of RANKL-induced angiogenesis, although OPG may also promote angiogenesis. (48,49) Because OPG did not change in response to the HEC, our results indicate that exogenous insulin does not acutely contribute to potential OPG-induced alterations in neurovascular function or bone turnover, but the source of increased OPG in T1D would need to be isolated to better inform its potential role in T1D-related complications.…”
Section: Discussionmentioning
confidence: 99%